2013
DOI: 10.1021/jm400638v
|View full text |Cite
|
Sign up to set email alerts
|

Toward Drugs for Protease-Activated Receptor 2 (PAR2)

Abstract: PAR2 has a distinctive functional phenotype among an unusual group of GPCRs called protease activated receptors, which self-activate after cleavage of their N-termini by mainly serine proteases. PAR2 is the most highly expressed PAR on certain immune cells, and it is activated by multiple proteases (but not thrombin) in inflammation. PAR2 is expressed on many types of primary human cells and cancer cells. PAR2 knockout mice and PAR2 agonists and antagonists have implicated PAR2 as a promising target in inflamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
86
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(86 citation statements)
references
References 192 publications
0
86
0
Order By: Relevance
“…Regulates Both mRNA and MicroRNA Expression-Numerous studies have shown that PAR-2 activation induces G␣-mediated signaling, mobilizing intracellular calcium and Nf-B signaling, and leading to increased expression of pro-inflammatory mRNAs (11)(12)(13)(14)(15). To determine whether PAR-2 activation in OSCC cell lines induces expression of candidate mRNAs known to be associated with inflammation in OSCC, expression of three pro-inflammatory genes known to be regulated downstream of PAR-2 activation was evaluated (27,39,40).…”
Section: Par-2 Activationmentioning
confidence: 99%
See 1 more Smart Citation
“…Regulates Both mRNA and MicroRNA Expression-Numerous studies have shown that PAR-2 activation induces G␣-mediated signaling, mobilizing intracellular calcium and Nf-B signaling, and leading to increased expression of pro-inflammatory mRNAs (11)(12)(13)(14)(15). To determine whether PAR-2 activation in OSCC cell lines induces expression of candidate mRNAs known to be associated with inflammation in OSCC, expression of three pro-inflammatory genes known to be regulated downstream of PAR-2 activation was evaluated (27,39,40).…”
Section: Par-2 Activationmentioning
confidence: 99%
“…Many studies have associated proteinase-activated receptor-2 (PAR-2) with both inflammation and tumor progression (11)(12)(13)(14)(15); however, the expression of PAR-2 in OSCC has not been evaluated. PAR-2 is a G protein-coupled receptor that is activated by trypsin-like serine proteinases.…”
mentioning
confidence: 99%
“…However, no improvement was observed. 182 Instead, this peptide (8) had similar potency to 2f-LIGRLI-NH 2 (7,EC 50 0.2 μM) in iCa 2+ release assay on HT29 cells. 182 In the same paper, a series of heterocycles and aromatic substitutents (9) were substituted for the serine residue of SLIGRLI-NH 2 (3), with 4-(2-methyloxazolyl), 5-isoxazolyl, 2-pyrazoyl, 2-pyridoyl, 3-pyridoyl, 2-benzofuranoyl, 2-naphthoyl, 2-benzothienyl, and others, all producing potent agonists with EC 50 0.1−0.3 μM (iCa 2+ , HT29 cells).…”
Section: ■ Par2 Agonistsmentioning
confidence: 83%
“…182 Instead, this peptide (8) had similar potency to 2f-LIGRLI-NH 2 (7,EC 50 0.2 μM) in iCa 2+ release assay on HT29 cells. 182 In the same paper, a series of heterocycles and aromatic substitutents (9) were substituted for the serine residue of SLIGRLI-NH 2 (3), with 4-(2-methyloxazolyl), 5-isoxazolyl, 2-pyrazoyl, 2-pyridoyl, 3-pyridoyl, 2-benzofuranoyl, 2-naphthoyl, 2-benzothienyl, and others, all producing potent agonists with EC 50 0.1−0.3 μM (iCa 2+ , HT29 cells). 182 Recently, the serine of SLIGRL-NH 2 was similarly replaced with closely related heterocycles, 2-aminothiazol-4-oyl (2-at) and 6-aminonicotinoyl (6-an), to also produce agonist analogues of 2f-LIGRLO-NH 2 (2), activating both Ca 2+ and MAPK signaling with comparable potency to the above.…”
Section: ■ Par2 Agonistsmentioning
confidence: 83%
See 1 more Smart Citation